Features of Kawasaki disease course in infants - O.S. Koreniuk; N.N. Kramarenko; S.H. Ivanus (Zaslavsky O.Yu., 2019)
Background. A large number of clinical masks and also insufficient vigilance of doctors regarding Kawasaki syndrome in a child with long-term fever impede timely diagnosis of Kawasaki syndrome. The purpose of the study was to increase the diagnostic efficiency of Kawasaki disease based on a retrospective analysis of its clinical course and outcomes in children under our supervision. Materials and methods. Case histories were analyzed in 7 children aged from 7 months to 6 years, who were treated in the cardiopulmonary department of Children's Clinical Hospital 2 in Dnipro. The diagnosis of Kawasaki disease was verified based on diagnostic criteria in accordance with the current clinical protocol. Routine research methods and echocardiography were performed for all patients. Results. The study revealed late diagnosis of Kawasaki disease, already at the stage of formation of coronary artery aneurysms, in 43 % of cases. The complexity of diagnosing Kawasaki syndrome was due to the lack of a full range of typical symptoms. The incomplete presentation was noted mainly in children of the first three years of life and included symptoms such as conjunctivitis, maculopapular rash, and oral lesions in various combinations. Echocardiography revealed coronary artery aneurysms in 57 % of cases, mostly in infants with incomplete presentation of Kawasaki disease. Against the background of therapy (intravenous immunoglobulin and aspirin), we observed a significant regression of coronary artery aneurysms in all patients. Conclusions. Infants most often have incomplete presentation of Kawasaki syndrome, which complicates its diagnosis. In this regard, prolonged fever in combination even with 2-3 typical signs should be an absolute indication for echocardiography with mandatory visualization of the coronary arteries.